2020
DOI: 10.3389/fendo.2020.599165
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP21 Acts as an Inhibitor of the Glucose-Stimulated Insulin Secretion Process

Abstract: ARHGAP21 is a RhoGAP protein implicated in the modulation of insulin secretion and energy metabolism. ARHGAP21 transient-inhibition increase glucose-stimulated insulin secretion (GSIS) in neonatal islets; however, ARHGAP21 heterozygote mice have a reduced insulin secretion. These discrepancies are not totally understood, and it might be related to functional maturation of beta cells and peripheral sensitivity. Here, we investigated the real ARHGAP21 role in the insulin secretion process using an adult mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This effect was also observed in 18-month-old rats ( Supplementary Figure S3 ) and this may be involved with an impaired glucose homeostasis, frequently observed in aged subjects. Previously, we suggested that an increased expression of the inducible nitric oxide synthase (iNOS), observed in the liver from 10-month-old mice, should be linked to the reduction in the hepatic IDE activity, because it was reported that nitric oxide (NO) inhibits insulin degradation by IDE ( 40 , 41 ). Here, the expression of iNOS was not increased, in fact, it was decreased in the liver from 18-month-old mice compared with controls ( Supplementary Figure S4 ), suggesting that other molecular mechanisms must be involved in the impairment on IDE function in the liver of these OLD mice ( 35 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was also observed in 18-month-old rats ( Supplementary Figure S3 ) and this may be involved with an impaired glucose homeostasis, frequently observed in aged subjects. Previously, we suggested that an increased expression of the inducible nitric oxide synthase (iNOS), observed in the liver from 10-month-old mice, should be linked to the reduction in the hepatic IDE activity, because it was reported that nitric oxide (NO) inhibits insulin degradation by IDE ( 40 , 41 ). Here, the expression of iNOS was not increased, in fact, it was decreased in the liver from 18-month-old mice compared with controls ( Supplementary Figure S4 ), suggesting that other molecular mechanisms must be involved in the impairment on IDE function in the liver of these OLD mice ( 35 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Arhgap21 has been suggested as a key regulator in various cellular pathways [ 122 ]. It was shown that ARHGAP21 had an inhibitory role during insulin secretion via glucose stimulation [ 123 ]. Since RP23-177L19.1 was also changed by the IGF-1 treatments in our study ( Figure 4 C) and other studies have shown that there is a regulatory relationship between protein-coding genes and lncRNA when they share the promoter sequence, it could be expected that there is also an association between Arhgap21 and this lncRNA.…”
Section: Discussionmentioning
confidence: 99%